영기선 테스트를 이용한 GNSS 수신기 조합별 코드의사거리 이중차분 잡음 특성 분석 - 박봉규; 박관동; Bong-Gyu Park; Kwan-Dong Park (Journal of Positioning, Navigation, and Timing, 2024)
Following the introduction of civilian navigation, the commercial Global Navigation Satellite System (GNSS) receivers' market has been expanding in various fields such as autonomous driving and smart cities. With improved receiver performance and widespread use of GNSS, the configurations of base and rover receivers are becoming more complex. As a result, user must consider combinations of base stations with different qualities, costs, and performances. To address these issues, we conducted zero-baseline tests to analyze the double-differenced code-pseudorange noise of various receiver combinations, ranging from low- to high-cost. The results showed that the noise varied depending on the receiver combination. Notably, receivers from the same manufacturer exhibited similar noise and positioning errors despite significant price differences. We also found that the double-differenced noise of all receiver combinations was correlated with the Carrier-to-Noise Density Ratio (C/N0), the satellite elevation angle, and the Doppler shift, and it did not perfectly follow a normal distribution. Further analysis based on Modified Allan Deviation (MDEV) showed that different types of noise were observed for each receiver combination and the double-differenced noise and positioning errors have similar statistical characteristics. From this study, the importance of receiver combinations and their various characteristics can be better understood.